Association Between Human Immunodeficiency Virus Viremia and Compromised Neutralization of Severe Acute Respiratory Syndrome Coronavirus 2 Beta Variant. (17th August 2022) - Hwa, Shi-Hsia; Snyman, Jumari; Bernstein, Mallory; Ganga, Yashica; Cele, Sandile; Muema, Daniel; Tan, Chee Wah; Khan, Khadija; Karim, Farina; Hanekom, Willem; Bernstein, Leslie; Kaufmann, Stefan H E; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may be associated with worse clinical outcomes in people with human immunodeficiency virus (HIV) (PWH). We report anti–SARS-CoV-2 antibody responses in patients hospitalized with coronavirus disease 2019 in Durban, South Africa, during the second SARS-CoV-2 infection wave dominated by the Beta (B.1.351) variant. Methods: Thirty-four participants with confirmed SARS-CoV-2 infection were followed up with weekly blood sampling to examine antibody levels and neutralization potency against SARS-CoV-2 variants. Participants included 18 PWH, of whom 11 were HIV viremic. Results: SARS-CoV-2–specific antibody concentrations were generally lower in viremic PWH than in virologically suppressed PWH and HIV-negative participants, and neutralization of the Beta variant was 4.9-fold lower in viremic PWH. Most HIV-negative participants and antiretroviral therapy–suppressed PWH also neutralized the Delta (B.1.617.2) variant, whereas the majority of viremic PWH did not. CD4 cell counts <500/μL were associated with lower frequencies of immunoglobulin G and A seroconversion. In addition, there was a high correlation between a surrogate virus neutralization test and live virus neutralization against ancestral SARS-CoV-2 virus in both PWH and HIV-negative individuals, but correlation decreased for the Beta variant neutralization in PWH. Conclusions: HIV viremia was associated with reduced Beta variant neutralization. This highlights the importance of HIV suppression in maintaining an effective SARS-CoV-2 neutralization response. Abstract : People with human immunodeficiency virus viremia elicited lower neutralizing antibody titers against infection with the Beta variant of severe acute respiratory syndrome coronavirus 2 and the majority were unable to cross-neutralize the Delta variant.